Rekapitulacja przemian w gospodarce turystycznej w województwie opolskim - Śmigielska, Maria (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Opole province, associated with industry and agricultural region during the transformation period, begins to appear as a attractive tourist region. There are significant changes on tourist service market as well on a supply side as demand side. Existing tourist potential of this area is wider used in creation of local product. One can observe a distinct improvement of quality of basic services (night's accommodation, meals, service organisation). On account of specific character of consumers of proposed offers (German and domestic segment - visiting relatives and friends) it might be well to make efforts towards consolidation of activities of subjects acting in tourist and around - tourist business to make more effective creation and forming a good regional tourist reputation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 135-145